PEMANFAATAN GENERATIVE AI DALAM PERANCANGAN WEBSITE SISTEM INFORMASI: STUDI KONSEPTUAL PENGGUNAAN GOOGLE STITCH DAN CHATGPT - Pariyasto, Sofyan; Mardiyah, Miftahul; Arfeni Warongan, Vicky; Astuti, Ermayanti; Lorenzza Sinaga, Alesia (Journal of Computer Science and Technology (JCS-TECH), 2026)
The rapid development of artificial intelligence, particularly Generative Artificial Intelligence (Generative AI), has significantly impacted various fields, including software development. This study aims to analyze the utilization of Generative AI in designing web-based information systems through a conceptual study approach using Google Stitch and ChatGPT. The research method employed is Research and Development (R&D), which includes stages of problem identification, literature review, case study, experimentation, and evaluation. During the experimentation phase, the capabilities of Generative AI in generating user interface designs and program code based on given prompts were explored. The results indicate that Google Stitch is capable of automatically generating website user interface designs with relatively representative visual quality, while ChatGPT can be utilized to assist in code development and the conversion of static HTML into more dynamic web applications. The integration of these tools contributes to improving efficiency in the design process of web-based information systems. However, the generated outputs still require further evaluation and refinement to meet the specific requirements of the system. This study provides a conceptual understanding of the integration of Generative AI in web-based information system design and highlights both the potential and limitations of its application in modern software development.